P186 Intrathoracic Lymph Node Tuberculosis – A Comprehensive Clinical Description. (10th November 2014) - Kow, KJH; Connell, DW; Singanayagam, A; Dafydd, D Ap; Jarvis, H; O'Donoghue, M; Wickremasinghe, MI; Lalvani, A; Kon, OM
Abstract : Background: Intrathoracic lymph node tuberculosis (ITLNTB) is an extra-pulmonary manifestation of tuberculosis (TB) and a predominant feature of primary TB in children. Historical literature supports the key role of lymph nodes in tuberculosis pathogenesis yet there is a paucity of literature describing ITLNTB in adults. Methods: This study comprehensively reviewed the clinical, radiological and pathological features of ITLNTB from 2009–2012 at a busy urban tuberculosis clinic. Results: 113 adult patients with ITLNTB were identified between 2009–2012. Patients were usually male, with a mean age of 41.5 ± 15.8 years and mostly from White, Black-African or Indian ethnic groups. 86% were non-UK born and most presented within 5–10 years of entering the country. 43% were asymptomatic. A subgroup of patients who were mycobacterial culture positive on endobronchial ultrasound sampling (EBUS) of intrathoracic lymph nodes were identified as patients with definite mycobacterial infection of the lymph nodes (n = 27). Comparisons between symptomatic and asymptomatic groups in the whole cohort and EBUS culture positive subgroup demonstrated significant associations between symptoms and disease dissemination (p = 0.0002 and p = 0.01 respectively); and symptoms and cytological response in the lymph nodes (p = 0.02 and p = 0.01 respectively), suggesting the presence of a spectrum of disease reflected in congruent clinical and pathological responses (Table 1). Comparisons between disease sites affected also showed a significant association between host response in the lymph nodes and disease dissemination (p = 0.006). The presence of radiological necrosis, number of affected nodal stations, and largest node size were significantly greater in symptomatic patients in the whole cohort; with a similar trend observed in the EBUS culture positive subgroup. In the EBUS culture positive subgroup, asymptomatic patients were identified significantly earlier following entry to the UK (p = 0.01). Discussion: This study provides the first comprehensive clinical description of ITLNTB in adults. There is a spectrum of disease based on clinical severity, disease phenotype and diagnostic and radiological findings. Host response in the lymph nodes is reflected by both symptom manifestation and disease dissemination, implicating the lymph nodes in a critical role in the natural history of TB infection. Finally, a subclinical phenotype was identified, suggesting an early stage of disease progression in TB.